Replication of the Association Between Keratoconus and Polymorphisms in PNPLA2 and MAML2 in a Han Chinese Population - Zhang, Jing; Li, Yue; Dai, Yiqin; Xu, Jianjiang (Frontiers in Genetics, 2020)
Keratoconus (KC) is a complex ocular disease that affected by both genetic and non-genetic triggers. A recent genome-wide association study (GWAS) identified a genome-wide significant locus for KC in the region of PNPLA2 (rs61876744), as well as a suggestive signal in the MAML2 (rs10831500) locus. In order to validate their findings, here we performed a replication study of the Han Chinese population, with 120 sporadic KC cases and 206 gender and age matched control subjects, utilizing the TaqMan SNP genotyping assays. SNP rs10831500, as well as two proxy SNPs for rs61876744, named rs7942159 and rs28633403 were subjected to genotyping. However, we did not find significant difference (P > 0.05) in all the three genotyped SNPs between KC cases and controls. Further meta-analysis on the previous four cohorts of white patients and this Han Chinese cohort showed a significant genetic heterogeneity within the replicated loci. Thus, the current study suggested that SNP rs61876744 (or its proxy SNPs) and rs10831500 might not be associated with KC susceptibility in this Han Chinese cohort, and a large-scale association analysis focusing on the loci should be warranted in further investigations.